The Randomized Controlled STRAWINSKI Trial: Procalcitonin-Guided Antibiotic Therapy after Stroke - Ulm, Lena; Hoffmann, Sarah; Nabavi, Darius; Hermans, Marcella; Mackert, Bruno-Marcel; Hamilton, Frank; Schmehl, Ingo; Jungehuelsing, Gerhard-Jan; Montaner, Joan; Bustamante, Alejandro; Katan, Mira; Hartmann, Andreas; et al. (Frontiers in Neurology, 2017)
Background: Pneumonia is among the most common acute complications after stroke and is associated with poor long-term outcome. Biomarkers may help identifying stroke patients at high risk for developing stroke-associated pneumonia (SAP) and to guide early treatment. Aims: This trial investigated whether Procalcitonin-ultrasensitive (PCTus) guided antibiotic treatment of SAP can improve functional outcome after stroke. Methods: In this international, multi-centre, randomised, controlled clinical trial with blinded assessment of outcomes, patients with severe ischemic stroke in the middle cerebral artery territory were randomly assigned within 40h after symptom onset to PCTus-based antibiotic therapy guidance in addition to stroke unit care, or standard stroke unit care alone. The primary endpoint was functional outcome at 3 months, defined according to the modified Rankin Scale (mRS) and dichotomised as acceptable (≤4) or unacceptable (≥5). Secondary end points included usage of antibiotics, infection rates, days of fever, and mortality. The trial was registered with ClinicalTrials.gov (Identifier NCT01264549). Results: In the intention-to-treat-analysis based on 227 patients (112 in PCT and 115 in control group) 197 patients completed the 3-month follow-up. Adherence to PCT guidance was 65%. PCT-guided therapy did not improve functional outcome as measured by mRS (Odds ratio 0.79; 95% CI 0.45-1.35, p=0.47). Pneumonia rate and mortality were similar in both groups. Days with fever tended to be lower (p=0.055) whereas total number of days treated with antibiotics were higher (p=0.004) in PCT compared to control group. A post hoc-analysis including all PCT values in the intention-to-treat population demonstrated a significant increase on the first day of infection in patients with pneumonia and sepsis compared to patients with urinary tract infections or without infections (p=<0.0001). Conclusion: PCTus-guided antibiotic therapy did not improve functional outcome at 3 months after severe ischemic stroke. PCT is a promising biomarker for early detection of pneumonia and sepsis in acute stroke patients.